Genetics and clinical response to warfarin and edoxaban in patients with venous thromboembolism. Issue 22 (8th July 2017) - Vandell, Alexander G; Walker, Joseph; Brown, Karen S; Zhang, George; Lin, Min; Grosso, Michael A; Mercuri, Michele F
Abstract : Objective: The aim of this study was to investigate whether genetic variants can identify patients with venous thromboembolism (VTE) at an increased risk of bleeding with warfarin. Methods: Hokusai-venous thromboembolism (Hokusai VTE), a randomised, multinational, double-blind, non-inferiority trial, evaluated the safety and efficacy of edoxaban versus warfarin in patients with VTE initially treated with heparin. In this subanalysis of Hokusai VTE, patients genotyped for variants in CYP2C9 and VKORC1 genes were divided into three warfarin sensitivity types (normal, sensitive and highly sensitive) based on their genotypes. An exploratory analysis was also conducted comparing normal responders to pooled sensitive responders (ie, sensitive and highly sensitive responders). Results: The analysis included 47.7% (3956/8292) of the patients in Hokusai VTE. Among 1978 patients randomised to warfarin, 63.0% (1247) were normal responders, 34.1% (675) were sensitive responders and 2.8% (56) were highly sensitive responders. Compared with normal responders, sensitive and highly sensitive responders had heparin therapy discontinued earlier (p<0.001), had a decreased final weekly warfarin dose (p<0.001), spent more time overanticoagulated (p<0.001) and had an increased bleeding risk with warfarin (sensitive responders HR 1.38 [95% CI 1.11 to 1.71], p=0.0035; highly sensitive responders 1.79 [1.09 to 2.99]; p=0.0252). Conclusion: In this study, CYP2C9 and VKORC1 genotypes identified patients with VTE at increased bleeding risk with warfarin. Trial registration number: NCT00986154.